2009
DOI: 10.2105/ajph.2008.149799
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Immigration and Acculturation Attributes With Oral Health Among Immigrants in New York City

Abstract: Immigrants' country of birth, length of stay in the United States, and age at immigration played important roles in their oral disease prevalence, independently of most known risk factors for oral diseases. Our findings emphasize the need for more studies to elucidate the complex relationships of ethnicity, socioeconomic status, and culturally influenced factors that impact immigrants' oral health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(106 citation statements)
references
References 24 publications
5
100
1
Order By: Relevance
“…Additionally, evidence is emerging to show that oral microbial communities play a critical role in the pathogenesis of oral cancer [5], [6]. It has been established that susceptibility to these diseases varies among ethnicities after controlling for socioeconomic, dietary, and other environmental factors [7], suggesting that indigenous oral microbial communities differ between ethnicities and that these differences may underlie the differential disease susceptibilities. Therefore, we investigated if variations in the composition of health-compatible oral biofilms can be attributable to an individual’s ethnic affiliation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, evidence is emerging to show that oral microbial communities play a critical role in the pathogenesis of oral cancer [5], [6]. It has been established that susceptibility to these diseases varies among ethnicities after controlling for socioeconomic, dietary, and other environmental factors [7], suggesting that indigenous oral microbial communities differ between ethnicities and that these differences may underlie the differential disease susceptibilities. Therefore, we investigated if variations in the composition of health-compatible oral biofilms can be attributable to an individual’s ethnic affiliation.…”
Section: Introductionmentioning
confidence: 99%
“…Cruz et al also report that other studies among immigrants from developing countries have found that the positive association between dental caries and socio-economic position (SEP) diminishes as duration in the industrialized country increases (7). It has been stressed that accounting for the diversity of cultural backgrounds is critical for patient-provider communication and plays a significant role in enhancing the quality of care and improving population health outcomes (8).…”
Section: Introductionmentioning
confidence: 92%
“…Acculturation has been considered an important factor in immigrants’ health seeking and preventive behaviors, yet studies relating it to oral health have provided contradictory results – some finding immigrants with less dental caries experience but others finding immigrants with more dental caries than similar native populations (7). Cruz et al also report that other studies among immigrants from developing countries have found that the positive association between dental caries and socio-economic position (SEP) diminishes as duration in the industrialized country increases (7).…”
Section: Introductionmentioning
confidence: 99%
“…Acculturation also may impact the ability of an individual to navigate the dental health care system (2, 6, 26, 27). Linguistic and cultural factors can play important roles in determining access to oral health services, as well as personal oral hygiene practices.…”
Section: How Acculturation Impacts Oral Health Of Immigrant Childrenmentioning
confidence: 99%